THE PERSPECTIVE OF STUDENT OF THE UNIVERSITY TOWARDS EDUCATION POLICY DURING COVID-19 PANDEMIC - Naria Fitriani; Nani Safuni; Said Iskandar Zulkarnain (Jurnal Transformasi Administrasi, 2021)
During the covid-19 pandemic spread Indonesia, educational system has been fluctuated. The face-to-face learning method soon is changed into the distance learning with the help of digital tools such as computer and internet. At the beginning, the compatible method was difficult to decide by the educational practitioners, particularly in Banda Aceh. However, the policy maker at higher education level especially at Syiah Kuala University has decided to use the mix method by implementing both classroom and online learning activity. In this study, the data were obtained through google form via social media such as WhatsApp. The participants who are in the 2nd and 4th semester were chosen in order to give their towards the new learning system. The results of this qualitative study indicated that most students (89.6%) agreed to the education policy. They (80%) also stated that they feel pleasure to learn with the mix methods in this semester. On the other hand, if the students could be able to choose without considering the side effects owing to the current pandemic situation, 51.8% of them preferred the face-to-face activity to online class.